7 Days of Garbage: Raising Awareness of Sustainability in the Classroom - Rodríguez, José-Víctor; Elizondo-Moreno, Aránzazu; Rodríguez-Rodríguez, Ignacio; Calderón-Fajardo, Víctor; Pardo-Quiles, Domingo (Radical Teacher, 2022)
Classroom activities aimed at raising awareness of sustainability should be an essential part of the curriculum to foster values and habits that generate an attitude of respect for the environment. The education system should bear in mind that appropriate environmental education will foster the next generation’s commitment towards our planet and an awareness of the need to care for it, thereby offering the benefit of a better future for all. The inculcation of environmental awareness among students is an indispensable element for the creation of ethically committed professionals who, across disciplinary fields, will build a new reality for sustainable development – far from the current overexploitation of resources and in harmony with nature, of which we are a part. As science teachers, last semester we proposed a classroom activity that can be developed within the framework of any subject in environmental sciences or as a cross-curricular exercise of any educational program. The objective of the activity was to get students to reflect on the huge amount of waste we generate. To this end, we considered the recent work by photographer Gregg Segal entitled "7 Days of Garbage", which shows families surrounded by the garbage they have produced over a week. This way, the activity fostered a series of ideas that led to an enriching and reflective debate by the students. This served to raise awareness of the importance of caring for our environment to ensure a sustainable future for the planet.